Quantitative Models for Value-Based Supply Chain Management - Brandenburg, Marcus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Supply chain management (SCM) strives for creating competitive advantage and value for customers by integrating business processes from end users through original suppliers.  However, the question of how SCM influences the value of a firm is not fully answered. Various conceptual frameworks that explain the coherence of SCM and company value, comprehended as value-based SCM, are well accepted in scientific research, but quantitative approaches to value-based SCM are found rather seldom. The book contributes to this research gap by proposing quantitative models that allow for assessing influences of SCM on the value of a firm. Opposed to existing models that limit the observation to chosen facets of SCM or selected value drivers, this holistic approach is adequate to • reflect configurational and operational aspects of SCM,  • cover all phases of the product life cycle, • financially compare value impacts of profitability-related and asset-related value drivers, and • assess influences of dynamics and uncertainties on company value.
1 Introduction -- 2 Terminology and Related Literature -- 3 Methodological Aspects -- 4 Content Analysis of Literature on Value-Based Supply Chain Management -- 5 Quantifying Value Impacts of Supply chain cost and working capital -- 6 Benchmarking Companies from the Fast Moving Consumer Goods Industry -- 7 Value-based Strategic Supply Chain Planning -- 8 Dynamics and Uncertainties in Tactical Supply Chain Design for New Product Introduction -- 9 Value Impact of Dynamics and Uncertainties in Tactical Supply Chain Design -- 10 Impact of Supply Chain Management on Company Value -- 11 Conclusion -- Appendices -- References.
Keywords: Production management; Economic theory; Operations research; Decision making; Operations Management; Economic Theory/Quantitative Economics/Mathematical Methods; Operations Research/Decision Theory